METABOLIC PROFILE OF COWS BLOOD, SICK WITH POSTPARTUM HYPOCALCEMIA - Юськів, Л. Л.; Влізло, В. В. (Scientific Progress & Innovations, 2013)
It was researched the content of 25-hydroxycholecalciferol (25-OND3), parathyroid hormone (PTH) and calcitonin (CT) and total calcium bounded with the protein and ultrafiltered inorganic phosphorus, magnesium, alkaline phosphatase, nonetherified fatty acids (NEFA), glucose and protein in the blood of cows suffering from postpartum hypocalcemia. It was found that in the blood of cows with clinical signs of postpartum hypocalcemia ,25- OHD3 content was higher, but the content of PTH and CT - lower in coparisant with healthy cows within 1-2 days after calving. However, in the blood of cows suffering from postpartum hypocalcemia was decreasing concentration of total, protein-linked and ultrafiltrates calcium, inorganic phosphorus, glucose, total protein and was increasing concentration of NEFA, magnesium and activity of alkaline phosphatase.